Neutrophil dysfunction varies with the stage of canine visceral leishmaniosis - Almeida, B. F M [UNESP]; Narciso, L. G. [UNESP]; Bosco, A. M. [UNESP]; Pereira, P. P. [UNESP]; Braga, E. T. [UNESP]; Avanço, S. V. [UNESP]; Marcondes, Mary [UNESP]; Ciarlini, Paulo Cesar [UNESP] (Elsevier, 2013)
Canine visceral leishmaniosis (CVL) causes a dependent-stage alteration in neutrophil oxidative metabolism. When production of reactive oxygen species (ROS) exceeds the antioxidant capacity of neutrophils, apoptosis is triggered, impairing the viability and function of these cells, which can predispose dogs to infection. However, the uremic condition observed in late-stage CVL can also alter the viability and function of human neutrophils. To more clearly understand this relationship, the apoptosis rate and oxidative metabolism of neutrophils from control dogs (n= 20) were compared to dogs in moderate (n= 15) and very severe (n= 15) stage CVL, classified according to LeishVet Consensus. To assess neutrophil oxidative metabolism, superoxide production was measured using the nitroblue tetrazolium reduction test (NBT) in isolated neutrophils. The apoptosis rate of neutrophils was estimated using the morphological method. Moderate-stage dogs presented increased superoxide production, while dogs with very severe stage CVL presented decreased superoxide production and an increase neutrophil apoptosis rate. Leishmaniosis causes differential neutrophil dysfunction according to disease stage. In moderate stage CVL, increased superoxide production is observed with no change in neutrophil viability. However, in very severe stage CVL, decreased superoxide production and increased apoptosis occur associated with uremia. © 2013 Elsevier B.V.
Keywords: Apoptosis; Leishmania spp.; Oxidative metabolism; Polymorphonuclear; nitroblue tetrazolium; superoxide; aerobic metabolism; animal cell; apoptosis; canine visceral leishmaniasis; cell assay; cell isolation; cell structure; cell viability; controlled study; disease association; disease classification; disease severity; dog disease; female; leukocyte function; leukocyte metabolism; male; neutrophil; neutrophil dysfunction; nonhuman; uremia; visceral leishmaniasis; Canis familiaris